Gene Variation at Immunomodulatory and Cell Adhesion Molecules Loci Impacts Primary Sjögren's Syndrome - Casadó-Llombart, Sergi; Gheitasi, Hoda; Ariño, Silvia; Consuegra-Fernández, Marta; Armiger-Borràs, Noelia; Kostov, Belchin; Ramos-Casals, Manuel; Brito-Zerón, Pilar; Lozano, Francisco (Frontiers in Medicine, 2022)
Primary Sjögren's syndrome (pSS) is an autoimmune disease triggered by a combination of environmental and host genetic factors, which results in the focal lymphocytic infiltration of exocrine glands causing eye and mouth dryness. Glandular infiltrates include T and B cell subsets positive for CD5 and/or CD6, two surface scavenger receptors involved in the fine-tuning of intracellular signals mediated by the antigen-specific receptor complex of T (TCR) and B (BCR) cells. Moreover, the epithelial cells of inflamed glands overexpress CD166/ALCAM, a CD6 ligand involved in homo and heterotypic cell adhesion interactions. All this, together with the reported association of functionally relevant single nucleotide polymorphisms (SNPs) of CD5, CD6, and CD166/ALCAM with the risk or prognosis of some immune-mediated inflammatory disorders, led us to investigate similar associations in a local cohort of patients with pSS. The logistic regression analyses of individual SNPs showed the association of CD5 rs2241002T with anti-Ro/La positivity, CD6 rs17824933C with neutropenia, and CD6 rs11230563T with increased leukopenia and neutropenia but decreased peripheral nervous system EULAR Sjögren's syndrome disease activity index (ESSDAI). Further analyses showed the association of haplotypes from CD5 (rs2241002T-rs2229177C) with anemia and thrombocytopenia, CD6 (rs17824933G-rs11230563C-rs12360861G) with cutaneous ESSDAI, and CD166/ALCAM (rs6437585C-rs579565A-rs1044243C and rs6437585C-rs579565G-rs1044243T) with disease susceptibility and several analytical parameters (anti-nuclear antibodies, neurological ESSDAI, and hematologic cytopenias). These results support the relevance of gene variation at loci coding for cell surface receptors involved in the modulation of T and B lymphocyte activation (CD5, CD6) and epithelial-immune cell adhesion (CD166/ALCAM) in modulating the clinical and analytical outcomes in patients with pSS.